ASSESSMENT OF THE QUALITY OF LEISURE PARKS USING THE IPA-KANO INTEGRATIVE APPROACH TO SATISFACTION, CASE TITO PARK, ALGERIA - Soraya Kentache; Aicha Boussoualim (International Journal of Innovative Technologies in Social Science, 2024)
Leisure parks provide innumerable benefits in terms of social well-being and economic advantages, hence the importance for managers to assess their condition and determine the beneficial actions to be taken. The physical and functional attributes of parks are key indicators of quality; especially, if they are inspected from the perspective of user satisfaction. Although previous studies have incorporated satisfaction, few have used management tools together in developing countries. This paper proposes the simultaneous use of importance-performance analysis (IPA) and the Kano model as an integrative approach to satisfaction to assess the quality of recreational parks. Tito Park in Algiers used as a case study, was the subject of two methods: first qualitative-exploratory by 116 interviews (2016-2017) on the sociocultural variables of visitors, and quantitative-empirical by IPA-Kano statistical analysis against 36 attributes hierarchized in 7 families of quality criteria. The results reveal a divergence of visitors’ opinions against these attributes within the same family of criteria; this is reinforced by a disparity between the degrees of importance and satisfaction that users allocate to them. This research offers a pragmatic tool to help with targeted and optimized decision-making and design as a means of requalification of the landscape. Because it elucidates the state of the recreational offer and points out the contextual characteristics to be promoted in order of priority by integrating the dimensions: perceptual and time. In the future, two or more parks can be compared using these or other tools by aggregating more attributes.